Molecular genetic analysis of 16 XP‐C patients from Germany: environmental factors predominately contribute to phenotype variations. Issue 1 (22nd November 2012) - Schäfer, Annika; Hofmann, Lars; Gratchev, Alexei; Laspe, Petra; Schubert, Steffen; Schürer, Anke; Ohlenbusch, Andreas; Tzvetkov, Mladen; Hallermann, Christian; Reichrath, Jörg; Schön, Michael P.; Emmert, Steffen
Abstract Patients belonging to xeroderma pigmentosum (XP) complementation group C comprise one‐third of all XP patients. Only four major reports compiled larger groups of XP‐C patients from southern Europe (12 pts), North America (16 pts) and Africa (14 and 56 pts) as well as their genetic background (46 XPC mutations). We identified 16 XP‐C patients from Germany. Interestingly, only five patients exhibited severe sun sensitivity. The mean age of XP diagnosis was 9.4 years, and the median age of the first skin cancer was 7 years. Neurological symptoms were absent in all but two patients. Primary fibroblasts from all 16 patients showed reduced post‐UV cell survival (mean: 50% vs 93% in normal cells) and reduced reactivation of an UV‐treated luciferase reporter gene (mean: 6.4% vs 30.7% in normal cells). XPC mRNA expression was also greatly reduced compared with normal cells (mean: 14.3%; range 8.3–25.7%) except in XP47MA (274.1%). All patients carried homozygous XPC mutations. Four mutations have been described previously: c.1747_1748delTG (found in 4/16), c.567 C>T (4/16), c.1839 C>T (1/16) and a complex insertion/deletion mutation in exon 9 (1/16). The novel frameshift mutations c.446_447delAG (2/16), c.1525insA (1/16) and c.2271delC (1/16) lead to truncated XPC proteins as does the novel nonsense mutation c.843C>T (1/16). XP47MA carries an interesting mutation (c.2538_2540delATC; p.Ile812del) resulting in an in‐frame single amino acid deletion. This mutation results in a classical XP phenotype, a non‐functional XPC protein, but elevated XPC mRNA expression. Our study indicates that extrinsic factors may contribute to XP‐C symptom severity due to nonsense‐mediated message decay.